A Study and Development of Web Based Social Interaction Platform with Assimilated Electronic Commerce and Weblog Functionalities - Rendy, Rendy (2010)
That this chapter initiates, it is expected capable to confer a valid comprehensive on current available web based social interaction platforms, electronic commerce and weblogs with a number of apparent instances and hereafter emphasise on respective functionalities. Comparison on functionalities among instances in the same category will be made, thus readers may obtain a distinct idea on each instances' characteristics.